Discovery of a 19F MRI sensitive salinomycin derivative with high cytotoxicity towards cancer cells. Issue 29 (21st March 2016) - Shi, Qiuyan; Li, Yu; Bo, Shaowei; Li, Xiaofei; Zhao, Peng; Liu, Qi; Yang, Zhigang; Cong, Hengjiang; Deng, Hexiang; Chen, Mingnan; Chen, Shizhen; Zhou, Xin; et al.
Abstract : The first 19 F MRI sensitive theranostic agent was discovered through site-specific modification of salinomycin and click library derivatization. Abstract : Salinomycin is a promising anti-cancer agent which selectively targets cancer stem cells. To improve its potency and selectivity, an analog library of salinomycin was generated by site-specific modification and CuAAc derivatization. Through a cytotoxicity analysis of the library, a fluorinated analog with high potency, selectivity, and 19 F MRI sensitivity was discovered as a novel theranostic agent.